Impact of Regulation (EU) No 2017/2393 on the legal organisation of the milk and milk products market - Lipińska, Izabela (Przegląd Prawa Rolnego, 2018)
The aim of this article was to answer the question whether and to what extent the amendments to the legal organisation of the milk and milk products market introduced as of 1 January 2018 contribute to improving the lives of milk producers and the development of the market. This refers to certain legal solutions adopted by the EU legislator which aim to strengthen the role of agricultural producers and their organisations in the agri-food supply chain. The amendments to Regulation 1308/2013 have not changed the organisational framework of the market, but addressed basically two issues – the obligation to conclude raw milk delivery contracts and contractual negotiations in this sector. The legal solutions adopted by the legislator are very positive. Written contracts, which are mandatory in many Member States, define and guarantee the producers’ rights and clearly indicate the obligations associated with the production process. In turn, entrusting the role of a negotiator of contract terms to producers’ representatives should be seen as recognition of their significant role in shaping the market in a manner adequate to its needs.